2019
DOI: 10.1073/pnas.1818572116
|View full text |Cite
|
Sign up to set email alerts
|

A scarcity mindset alters neural processing underlying consumer decision making

Abstract: Not having enough of what one needs has long been shown to have detrimental consequences for decision making. Recent work suggests that the experience of insufficient resources can create a “scarcity” mindset; increasing attention toward the scarce resource itself, but at the cost of attention for unrelated aspects. To investigate the effects of a scarcity mindset on consumer choice behavior, as well as its underlying neural mechanisms, we used an experimental manipulation to induce both a scarcity and an abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 52 publications
0
50
1
1
Order By: Relevance
“…Although the current study did not directly examine mothers' underlying reasons for restrained eating in the context of increases in household food insecurity, the additional cognitive capacity required to inhibit eating likely increases psychological stress on low-income mothers, 9,51 increasing risk for further mental health concerns among an already health disparate population, which should be of concern to practitioners and public health officials alike.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although the current study did not directly examine mothers' underlying reasons for restrained eating in the context of increases in household food insecurity, the additional cognitive capacity required to inhibit eating likely increases psychological stress on low-income mothers, 9,51 increasing risk for further mental health concerns among an already health disparate population, which should be of concern to practitioners and public health officials alike.…”
Section: Discussionmentioning
confidence: 97%
“…1.1 | Household food insecurity, maternal restrained eating, and child feeding practices Both theory and empirical research suggest that the perception of limited resources (eg, money, time, and food) can have a profound impact on decision-making and health behaviors that impact obesity risk for mothers and their children. 9,10 According to the family stress model, 11 household food insecurity is an economic pressure that affects parents' psychological stress, which in turn affects parenting behavior. 12…”
Section: Introductionmentioning
confidence: 99%
“…The effect of altering only β (rationality) or both µ (memory) and β (rationality) on the susceptibility of cattle to RVF and CBPP is meaningful. Modeling the effect of dynamic cognitive capacity, whether uniform or non-uniform across a population, on a range of decision contexts is supported by detailed experimental and non-experimental findings [(Choi and Iles, under review); (36)]. The incorporation of an RFIM for decision making within an ABM, as demonstrated by the PastoralScape model, provides a clear avenue to extend livestock disease modeling (6).…”
Section: Discussionmentioning
confidence: 99%
“…The parameterisation of head-of-household memory and "rationality" provides flexibility to model two important aspects of cognitive ability (32-34). Human cognitive ability or capacity are believed to change over time due to stress, anxiety and the perception of these (10,35,36). According to Mullainathan and Shafir's "scarcity thesis, " perceptions of household financial stress act as a tax on cognitive capacity [(9); (Iles et al, under review)].…”
Section: Basic Principlesmentioning
confidence: 99%
“…The link between resource scarcity and cognitive scarcity is likely to be a fundamental part of human psychology. For instance, Huijsmans et al (2019) found in an fMRI study that the inducement of scarcity vs. abundance mindsets activated different neural networks associated with valuation and goal-directed choice. Given its underlying neurological basis, attentional focus and neglect due to scarcity are likely to shape heterogeneous domains of behavior.…”
Section: Introductionmentioning
confidence: 99%